Determinants of users' perception of and satisfaction with a home energy storage system under a leasing scheme in Japan. (February 2022) - Abe, Naoya; Ishida, Junya
Highlights: Study focused on a residential energy storage system leasing scheme in Japan Perceived financial benefits greatly impact satisfaction with the scheme Some respondents (25.8%) might not obtain financial benefits from ESS leasing Sense of security found to be non-significant in impacting user satisfaction Building a deeper understanding of such energy systems crucial for their diffusion Abstract: This study focussed on a leasing scheme for home energy storage systems (ESS) in Japan. Based on a review of the relevant articles related to ESS and leasing schemes in general, it proposes a leasing scheme for ESS that reduces the initial investment cost for ESS users. In this process, the study focussed on two objectives: investigating the determinants of the perception and satisfaction of users of ESS with the system, and clarifying the relationship between the satisfaction level and subjective judgment of the economic benefits of ESS under the leasing scheme. To these ends, questionnaire surveys were employed, and logit model analysis and cluster analysis were performed. The results showed that most ESS lease users were satisfied mainly because of the perceived financial benefits. Additionally, the satisfaction level increased with the perceived economic benefits, satisfaction with having new equipment, and understanding of ESS. For further diffusion and sustainable use of ESS, it is important that users understand the advantages of ESS, which can bring financial benefits and provide opportunities for a deeper understanding of the system.